1990
DOI: 10.1021/bi00462a015
|View full text |Cite
|
Sign up to set email alerts
|

A sensitive genetic assay for the detection of cytosine deamination: determination of rate constants and the activation energy

Abstract: Previously it has not been possible to determine the rate of deamination of cytosine in DNA at 37 degrees C because this reaction occurs so slowly. We describe here a sensitive genetic assay to measure the rate of cytosine deamination in DNA at a single cytosine residue. The assay is based on reversion of a mutant in the lacZ alpha gene coding sequence of bacteriophage M13mp2 and employs ung- bacterial strains lacking the enzyme uracil glycosylase. The assay is sufficiently sensitive to allow us to detect, at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
393
5
8

Year Published

1996
1996
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 477 publications
(428 citation statements)
references
References 26 publications
22
393
5
8
Order By: Relevance
“…In experiments comparable with those reported by earlier investigators (22,23), we extended those measurements to include cytosine residues in single-stranded DNA, using a phagemid in which we sequenced an insert representing the gene of the HIV-1 protease to compare the rates of cytosine-deaminating events with those of other potentially mutagenic reactions in single-stranded DNA (ssDNA).…”
Section: Hiv-1 Proteasementioning
confidence: 82%
“…In experiments comparable with those reported by earlier investigators (22,23), we extended those measurements to include cytosine residues in single-stranded DNA, using a phagemid in which we sequenced an insert representing the gene of the HIV-1 protease to compare the rates of cytosine-deaminating events with those of other potentially mutagenic reactions in single-stranded DNA (ssDNA).…”
Section: Hiv-1 Proteasementioning
confidence: 82%
“…This can be associated with the presence of CpG methylation, which can act as a repressive epigenetic mark in some contexts (34). Cytosine methylation makes the base susceptible to deamination, resulting in C-to-T transitions (35,36). Thus, CpG frequency can be used as an indication of the extent of methylation.…”
Section: Resultsmentioning
confidence: 99%
“…27 The non-transcribed strand is transiently single-stranded, in contrast to the transcribed strand that may largely be protected by the R-loop. Spontaneous (5-methyl)cytosine deamination in singlestrand DNA is increased about 100-fold, 28 which provides a mechanistic explanation for this TAP pathway. Later work has revealed that also the frequency of spontaneous nucleotide transversions at the nontranscribed strand is increased.…”
Section: Transcription-associated Point Mutagenesis (Tap)mentioning
confidence: 99%